Stories of Aroostook : the best of Echoes magazine - Olmstead, Kathryn; Olmstead, Kathryn (Yarmouth, Maine : Islandport Press, 2020)
For nearly thirty years, Echoes magazine brought the culture, heritage, landscape and people of Aroostook County to readers in Maine and across America. Kathryn Olmstead, who founded the magazine with Gordon Hammond, once said: "A place like Aroostook County is the kind of place most people can only imagine." Olmstead and Hammond set out to share the experience of living in a such a remarkable region, but what started as a portrait of a place, quickly evolved into a magazine with a mission--affirming the value of living simply with respect for nature, not as a way of life. Stories of Aroostook is a collection of stories from the pages of the beloved quarterly magazine, all capturing the spirit and sense of place that makes Aroostook County unforgetable.
Keywords: Editors -- Maine; Imprints (Publishers' and printers' statements) -- Maine -- Yarmouth; Aroostook County (Me.) -- Social life and customs